An Improved RSP Method to Detect HpaI Polymorphism in the Apolipoprotein C-1 Gene Promoter - Lavoie Tera; Gabriel Curt; Gao Li; Ye Shui (BMC Medical Genetics, 2002)
Abstract Background An apolipoprotein C1 gene promoter polymorphism (CGTT insertion at position -317) is associated with familial dysbetalipoprotemia, cardiovascular diseases, and Alzheimer's disease. Restriction site polymorphism (RSP) assays were previously established to detect this polymorphism. In this study, we introduce an improved RSP assay to detect this polymorphism. Methods This method included newly designed primers and only one round of PCR amplification which yields one short and specific APOC1 fragment followed by HpaI digestion. Briefly, It consists of three steps: 1) one round of PCR amplification of DNA sample, 2) HpaI enzyme digestion of PCR products, and 3) electrophoresis on an agarose gel to visualize the genotypes. This improved RSP method was applied to genotype 92 human samples collected from The Johns Hopkins Hospital. Results The observed allele frequencies for H1 and H2 from 92 genotyped human subjects were 0.707 and 0.293 respectively. The H2 allele frequency in the black subjects (0.350) was significantly (p = 0.024) higher than that in the white subjects (0.177). This method was more economical and convenient than the methods previously reported to detect this mutation in the APOC1 gene. Conclusions This assay will be readily applied to screen large sample sizes for population studies in a simple and cost effective way.